Significance of Photosynthetic Characters in the Evolution of Asian Gnetum (Gnetales) - Deng, Nan; Hou, Chen; Liu, Caixia; Li, Minghe; Bartish, Igor; Tian, Yuxin; Chen, Wei; Du, Changjian; Jiang, Zeping; Shi, Shengqing (Frontiers in Plant Science, 2019)
Gnetum is a genus in the Gnetales that has a unique but ambiguous placement within seed plant phylogeny. Previous studies have shown that Gnetum has lower values of photosynthetic characters than those of other seed plants, but few Gnetum species have been studied, and those that have been studied are restricted to narrow taxonomic and geographic ranges. In addition, the mechanism underlying the lower values of photosynthetic characters in Gnetum remains poorly understood. Here, we investigated the photosynthetic characters of a Chinese lianoid species, i.e., Gnetum parvifolium, and co-occurring woody angiosperms growing in the wild, as well as seedlings of five Chinese Gnetum species cultivated in a greenhouse. The five Gnetum species had considerably lower values for photosynthesis parameters (net photosynthetic rate, transpiration rate, intercellular CO2 concentration, and stomatal conductance) than those of other seed plant representatives. Interrelated analyses revealed that the low photosynthetic capacity may be an intrinsic property of Gnetum, and may be associated with its evolutionary history. Comparison of the chloroplast genomes (cpDNAs) of Gnetum with those of other seed plant representatives revealed that 17 coding genes are absent from the cpDNAs of all species of Gnetum. This lack of multiple functional genes from the cpDNAs probably leads to the low photosynthetic rates of Gnetum. Our results provide a new perspective on the evolutionary history of the Gnetales, and on the ecophysiological and genomic attributes of tropical biomes in general. These results could also be useful for the breeding and cultivation of Gnetum.